Inflammation in patients with opiate use disorder: neutrophil / lymphocyte, platelet / lymphocyte, monocyte / lymphocyte ratios and mean platelet volume - Kulu, Müberra; Özsoy, Filiz; Demir, Bahadır (Journal of Dependence, 2023)
Objective: The aim of this study was to retropeectivelyt analyse the inflammation markers such as neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLO), and monocyte-lymphocyte ratio (PLO), of the patients with opiate use disorder (OUD) by comparing them with healthy controls. Method: 201 people (101 people OUD, 100 control) were included in the study. A demographic data form containing demographic data such as age and gender of all participants was created. Afterwards, laboratory parameters evaluated by complete blood count were examined. Results: All participants were male and mean age 30.68±10.60. Hemoglobin values 14.78±1.29, hematocrit values 44.02±3.70 for patients group. Erythrocyte 5.00±0.39 and RDW-SD values 43.90±4.26; These values were higher in patients than in healthy controls. NLR, MLR and PLR values were lower in the patient group compared to the controls. Conclusion: There are changes in some inflammatory parameters in OUD patients. Complications that may occur due to these changes in inflammatory parameters; should be considered in both the treatment plan and the evaluation of the patient’s symptoms.